The business case for equal opportunities : equality, equity and egalitarianism - O'Malley, Siobhan (Cranfield University, 2001)
The research project reported in this thesis concerned the business case for equal opportunity in the workplace. The project comprised three distinct but related studies: 1. Study I was a qualitative investigation into which variables employees perceived to be associated with equal opportunity in the workplace. The over-arching fmding was that participants had a low awareness of equal opportunity and perceived general fairness (organisational egalitarianism) to be more important than equal opportunity per se. Job attitude outcome variables ofjob satisfaction, organisational commitment, intention to leave and perceived performance were proposed. 2. Study 2 qualitatively explored the issues associated with the business case for equal opportunity as perceived by equality practitioners. Results detailed perceptions of equal opportunity climate, employer motivations and the problems associated with translating equal opportunity policy into practice. 3. Study 3 sought to quantitatively measure the impact of equal opportunity and organisational egalitarianism on the job attitude outcome variables identified by studies I and 2. A questionnaire, the Social Atmosphere at Work Survey, was constructed and piloted to measure the perceived equal opportunity climate, the outcome variables and an individual difference construct, equity sensitivity. Results indicated that equal opportunity significantly contributed to job satisfaction, organisational commitment, intention to leave and perceived workgroup, effectiveness. Organisational egalitarianism however proved a stronger predictor of these outcome variables than perceived equal opportunity level, as suggested by the qualitative results. Equity sensitivity did not significantly moderate any of these relationships.